УПРАВЛЕНИЕ ИННОВАЦИЯМИ В СФЕРЕ ИНФОРМАЦИОННО-КОММУНИКАЦИОННЫХ ТЕХНОЛОГИЙ (International Journal of Innovative Technologies in Economy, 2018)
In the given article theoretical foundations of innovation management, in particular, in the field of information and communication technologies are described. The field of information and communication technologies around the world is developing at a rapid pace, at the same time being introduced into all spheres of activity. Globalization has enabled the development of digital marketing and digital diplomacy, research centers are developing original ideas, offering breakthrough solutions, new proposals, the era of messenger advancement is developing, business needs marketing and new generation managers. The life cycle of innovative products in the field of information and communication technologies is shrinking at a rapid pace and there is a need for effective management of innovation in this industry. An analysis was carried out to identify the relationship between profit and investments in innovative activity by the example of the national operator of Uzbekistan "Uzbektelecom" JSC. A regression model of the relationship between expenditure and investment in innovation has been identified.Also analysis of development pace of information and communication technologies in Uzbekistan, the connection between the development of ICT and innovation are described. Proposals and measures on development of management of innovative activity in the country are also given.